A time domain anti-jamming processing algorithm for GNSS ranging receiver - Li, Xianghao; Lu, Zukun; Chen, Feiqiang; Liu, Zhe; Yuan, Muzi; Ou, Gang (Frontiers in Physics, 2022)
The traditional anti-jamming algorithm will lead to the deviation of the GNSS receiver's ranging value, which has become the main obstacle to the improvement of the accuracy of the high-precision ranging receiver. Traditional time-domain anti-jamming (TDAJ) algorithms can cause signal distortion, resulting in ranging bias. This study aims to solve this problem by proposing a design method for adding preprocessing filters in time-domain anti-jamming navigation receivers. In this method, an optimal order filter for adaptively correcting signal distortion is designed according to the time-domain anti-jamming filter coefficients. The experimental results show that the algorithm proposed in this paper can effectively solve the problem of ranging bias caused by the traditional TDAJ algorithm. The algorithm can be widely used in dedicated satellite missions that require high positioning accuracy, such as navigation signal monitoring receiver, satellite payload receivers, and precision approach and landing system for carrier-based aircraft.